Relational Knowing and Epistemic Injustice: Toward a Theory of Willful Hermeneutical Ignorance - Pohlhaus, Gaile (Hypatia, 2012)
I distinguish between two senses in which feminists have argued that the knower is social: 1. situated or socially positioned and 2. interdependent. I argue that these two aspects of the knower work in cooperation with each other in a way that can produce willful hermeneutical ignorance, a type of epistemic injustice absent from Miranda Fricker's Epistemic Injustice. Analyzing the limitations of Fricker's analysis of the trial of Tom Robinson in Harper Lee's To Kill a Mockingbird with attention to the way in which situatedness and interdependence work in tandem, I develop an understanding of willful hermeneutical ignorance, which occurs when dominantly situated knowers refuse to acknowledge epistemic tools developed from the experienced world of those situated marginally. Such refusals allow dominantly situated knowers to misunderstand, misinterpret, and/or ignore whole parts of the world.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; histoire et politique; ignorance herméneutique; injustices herméneutiques; injustices épistémiques; justice sociale; patriarcat; philosophie; privilèges; racisme; sciences humaines; systèmes d'oppressions; thématiques; éthique

Adoption internationale: L’exode des berceaux ? - St-Amand 1, Nérée (Nouvelles pratiques sociales, 2012)
Keywords: 2000 à aujourd'hui; approches et analyses; corps; cours; discipline; justice reproductive; maternité; premier cycle; privilèges; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc3113; sociologie; sud global; système colonial; systèmes d'oppressions; thématiques; travail